The concept of love and the political in Kantian political ethics - Quiroga, Noelia Eva (Anales del Seminario de Historia de la Filosofía, 2024)
The purpose of this work is to offer an ethical-political reading of love in the Kantian virtue ethics expressed in Religion within the Boundaries of Mere Reason and in The Metaphysics of Morals. To this end, in the first place, I will study the problem that self-love presents, understood as a possible obstacle to love towards others, with whom we interact. Secondly, I will study how the idea of practical love in Kantian virtue ethics, gives rise, in the sphere of relationships with others, to the duty to love one’s neighbor and contribute to his happiness. Finally, I will study how the Kantian political ethics, embodied in the idea of the ethical community, expresses an ethics of love that allows to counteract the excess of self-love.
Keywords: Kant; self-love; love towards others; beneficence; ethical community